Dynamic variability of biogeochemical ratios in the Southern California Current System. Issue 7 (14th April 2014) - Martz, Todd; Send, Uwe; Ohman, Mark D.; Takeshita, Yuichiro; Bresnahan, Philip; Kim, Hey‐Jin; Nam, SungHyun
Abstract: We use autonomous nitrate (NO3 − ), oxygen (O2 ), and dissolved inorganic carbon (DIC) observations to examine the relationship between ratios of C:N:O at an upwelling site in the Southern California Current System. Mean ratios and 95% confidence intervals observed by sensors over 8 months were NO3 − :O2  = −0.11 ± 0.002, NO3 − :DIC = 0.14 ± 0.001, and DIC:O2  = −0.83 ± 0.01, in good agreement with Redfield ratios. Variability in the ratios on the weekly time scale is attributable to shifts in biological demand and nutrient availability and shown to exhibit a spectrum of values ranging from near 100% New Production to 100% Regenerated Production. Key Points: Chemical sensors provide a means to observe the Redfield ratios Redfield ratios vary on the weekly timescale The f ratio ranges from 100% New to 100% Regenerated Production